IMPACTS OF FINTECH ON FINANCIAL INCLUSION: THE CASE OF SUB-SAHARAN AFRICA - Wulli Faustin Djoufouet; Thierry Messie Pondie (Copernican Journal of Finance & Accounting, 2023)
The objective of this paper is to determine the impact of FinTech on the financial inclusion of populations in sub-Saharan Africa where financial education is still low. To do so, data were collected on a sample of 35 countries over a period from 2011 to 2020. Estimates were made using two-stage least squares models and the Lewbel 2LS model. It is clear from the results that fintech contributes significantly to the financial inclusion of people in sub-Saharan Africa. Mobile phone ownership facilitates the use of financial services. It is noted that a 1% increase in the number of people using a phone would contribute to a 0.67% increase in the financial inclusion rate. The Driscoll-Kraay technique consolidated these results by showing that with 1% of people having access to fintech tools, there is an improvement in the financial inclusion rate of about 0.70%.